E-banking Service Quality dan E-trust serta Implikasinya pada E-customer Satisfaction dan E-customer Loyalty - Fani Firmansyah; Puji Endah Purnamasari; Maretha Ika Prajawati (Fakultas Ekonomi, UIN Maliki Malang, 2022)
This study aims to make a significant contribution to the banking marketing literature and to explain how the dimensions of e-service quality and e-trust are used as predictors of e-satisfaction and consequently increase e-loyalty. The population in this study consisted of banking customers, both Islamic banking and conventional banking in Malang City. The sample is part of the number and characteristics of the population. The sampling technique in this research is purposive sampling. The results of the study show that the services provided by banking in Malang City in the form of online transactions are able to have a good impact on the satisfaction felt by customers, so that because customers are satisfied they will always use these services, especially at this time which is very much needed considering the restrictions on community activities due to there is a COVID-19 pandemic. Customer confidence in online media provided by banks in Malang City has a positive influence on the satisfaction felt by customers, which in the end customers will feel loyal and return to using these services during this covid-19 pandemic.